2016
DOI: 10.1002/vms3.32
|View full text |Cite
|
Sign up to set email alerts
|

A phase I clinical study to evaluate safety of orally administered, genetically engineeredSalmonella entericaserovarTyphimuriumfor canine osteosarcoma

Abstract: We conducted a prospective phase I study to evaluate safety of an orally administered Salmonella encoding IL‐2 (SalpIL2) in combination with amputation and adjuvant doxorubicin for canine appendicular osteosarcoma. Efficacy was assessed as a secondary measure. The first dose of SalpIL2 was administered to 19 dogs on Day 0; amputation was done after 10 days with chemotherapy following 2 weeks later. SalpIL2 was administered concurrent with chemotherapy, for a total of five doses of doxorubicin and six doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 45 publications
(51 reference statements)
1
25
0
Order By: Relevance
“…98 Oral administration of Salmonella typhimurium genetically engineered to express human IL-2 to dogs also appeared to be safe and well tolerated. 116 Bacille Calmette-Guérin (BCG), attenuated Mycobacterium bovis, has also been administered to dogs with OSA and may improve survival, although the mechanisms of immune response to BCG are not completely understood. 91,92 xenogeneic hamster cells modified to secrete human GM-CSF and IL-2.…”
Section: Veterinary Clinical Trialsmentioning
confidence: 99%
“…98 Oral administration of Salmonella typhimurium genetically engineered to express human IL-2 to dogs also appeared to be safe and well tolerated. 116 Bacille Calmette-Guérin (BCG), attenuated Mycobacterium bovis, has also been administered to dogs with OSA and may improve survival, although the mechanisms of immune response to BCG are not completely understood. 91,92 xenogeneic hamster cells modified to secrete human GM-CSF and IL-2.…”
Section: Veterinary Clinical Trialsmentioning
confidence: 99%
“…Despite the complex safety considerations, the FDA has allowed several clinical trials with tumor-targeting bacteria and bacterial vaccines designed to elicit a systemic response (Table 4 ) [ 10 , 149 – 152 ]. Clinical studies on companion dogs with spontaneous tumors have also been conducted [ 10 , 153 , 154 ]. The tumor-targeting bacterial strains tested in both canine and human studies showed reasonable safety profiles in general and promising antitumor activities in some studies.…”
Section: Lessons Learned From Clinical Studiesmentioning
confidence: 99%
“…A phase I trial of VNP20009 was performed in dogs with a variety of malignancies and 41 dogs received intravenous administration of VNP20009 at escalating doses weekly or biweekly with an objective and biological overall response rate of 15% and 37%, respectively . A prospective phase I study of 19 dogs was also performed to evaluate safety of an orally administered Salmonella encoding IL‐2 (SalpIL2) in combination with amputation and adjuvant doxorubicin chemotherapy for canine appendicular osteosarcoma . While SalpIL2 was well tolerated, it did not provide a clear benefit compared with a historical control group of dogs treated with amputation and adjuvant doxorubicin/carboplatin …”
Section: Immunotherapy Approaches For Canine Sarcomasmentioning
confidence: 99%
“…A prospective phase I study of 19 dogs was also performed to evaluate safety of an orally administered Salmonella encoding IL‐2 (SalpIL2) in combination with amputation and adjuvant doxorubicin chemotherapy for canine appendicular osteosarcoma . While SalpIL2 was well tolerated, it did not provide a clear benefit compared with a historical control group of dogs treated with amputation and adjuvant doxorubicin/carboplatin …”
Section: Immunotherapy Approaches For Canine Sarcomasmentioning
confidence: 99%